Internet Prospective Study - Jesus Antonio Alvarez-Cedillo; Elizabeth Acosta Gonzaga; Mario Aguilar-Fernández; Patricia Perez-Romero (Institute of Advanced Engineering and Science, 2017)
The Internet is currently the largest network of communication worldwide and is where technological advances could be observed. The original creation of the Internet was based on the idea that this network would be formed mainly by multiple independent networks with an arbitrary design. The Internet is the place where all countries communicate and disseminate information in real time, this phenomenon directly affects economies, businesses, and society. This article shows what the future of the Internet is, our research carries out a qualitative prospective analysis on projects and investigations in which the scientific community is currently working, the information is analyzed, and the highlighted topics are shown.